Ring Cavity Multi-wavelength Brillouin-Erbium Fiber Laser Utilizing a Fiber Bragg Grating Filter - M. N. Mohd, Nasir; Z., Yusoff; M. H., Al-Mansoori; H. A. Abdul, Rashid; P. K., Choudhury (2008)
An efficient multi-wavelength Brillouin-erbium fiber laser in a ring cavity is presented. Up to 31 Brillouin Stokes lines with SNR of more than 20 dB could be generated from the experimental setup which utilizes a broadband fiber Bragg grating filter as the cavity feedback. Only 0.2 dBm of Brillouin pump and 70 mW of the 980 nm LD powers were consumed to generate the output channels with constant spacing of 0.088 nm.